Employer Knowledge of and Attitudes toward Employees who Are Blind or Visually Impaired. (May 2014) - McDonnall, Michele Capella; O'Mally, Jamie; Crudden, Adele
Introduction: The study presented here investigated employers' knowledge about how persons who are blind or visually impaired perform typical job tasks (that is, use accommodations), how this knowledge relates to employers' attitudes about these individuals as employees, and where employers seek help with job accommodations. Methods: Businesses from four states were contacted by telephone to request participation; surveys were completed by 160 randomly selected businesses and 37 businesses referred by vocational rehabilitation agencies, yielding a total sample of 197. A 5-item instrument measured employers' knowledge about how blind or visually impaired persons complete typical job tasks, and an 11-item instrument measured employers' attitudes toward blind or visually impaired persons as employees. Results: A majority of employers (67%) could not identify how blind or visually impaired persons perform any of the typical job tasks. Employers referred by vocational rehabilitation agencies were more likely to identify correct strategies than employers in the randomly identified sample. Knowledge levels were associated with attitudes toward blind or visually impaired persons as employees. Only 8.8% of the randomly identified sample cited an appropriate source of information about accommodations; 49.7% cited a secondary source and 41.5% were not able to identify an appropriate source. Discussion: Most employers have limited or no knowledge about how blind or visually impaired persons perform routine job tasks. Those employers with greater levels of knowledge also had more positive attitudes toward blind or visually impaired persons as employees. It is encouraging that many employers were aware of an appropriate or secondary source of information about accommodations, and would therefore be likely to find such information if needed. Implications for practitioners: Providing education to employers and human resources professionals about job accommodations, including where to find additional information, is necessary and would be an appropriate strategy to use when interacting with employers.